Jacques Rancière, El tiempo del paisaje. Los orígenes de la revolución estética. Akal, 2023. 128 pp. - Verónica Uribe Hanabergh (Hart)
Reseña. Jacques Rancière, El tiempo del paisaje. Los orígenes de la revolución estética. Akal, 2023. 128 pp.